A novel copper precursor for electron beam induced deposition - Haverkamp, Caspar; Sarau, George; Polyakov, Mikhail N.; Utke, Ivo; Puydinger dos Santos, Marcos V.; Christiansen, Silke; Höflich, Katja (Beilstein Journal of Nanotechnology, 2018)
A fluorine free copper precursor, Cu(tbaoac)2 with the chemical sum formula CuC16O6H26 is introduced for focused electron beam induced deposition (FEBID). FEBID with 15 keV and 7 nA results in deposits with an atomic composition of Cu:O:C of approximately 1:1:2. Transmission electron microscopy proved that pure copper nanocrystals with sizes of up to around 15 nm were dispersed inside the carbonaceous matrix. Raman investigations revealed a high degree of amorphization of the carbonaceous matrix and showed hints for partial copper oxidation taking place selectively on the surfaces of the deposits. Optical transmission/reflection measurements of deposited pads showed a dielectric behavior of the material in the optical spectral range. The general behavior of the permittivity could be described by applying the Maxwell–Garnett mixing model to amorphous carbon and copper. The dielectric function measured from deposited pads was used to simulate the optical response of tip arrays fabricated out of the same precursor and showed good agreement with measurements. This paves the way for future plasmonic applications with copper-FEBID.
Keywords: copper; Cu(tbaoac)2; focused electron beam induced deposition; nanostructures; optical properties